The Role of Mana in Dharaniya Vega: A Kriyasharir Perspective - Shruti Ramu Raut; Simant Sourav (AYUSHDHARA, 2025)
The Ayurvedic principle of Vega encompasses natural instincts that need to be appropriately regulated to ensure overall health. Specifically, Dharaniya Vega refers to those urges that require mindful control to avoid physiological and psychological disruptions. The management of Dharaniya Vega is intricately connected to the workings of Mana (mind), which is crucial for regulating emotions and cognitive functions. Ayurveda asserts that an imbalance in Mana can lead to either overindulgence in or repression of Dharaniya Vega, which may result in various psychosomatic conditions such as stress, anxiety, depression, cardiovascular problems, and metabolic disorders. This review examines the influence of Mana on the regulation of Dharaniya Vega from a Kriyasharir (physiological) viewpoint, emphasizing its significance for overall health. It combines perspectives from Ayurvedic texts, contemporary neurophysiology, and psychological research to provide a holistic understanding of the interactions between mind and body in Vega regulation. The characteristics of Mana—Sattva, Rajas, and Tamas- are explored to elucidate their roles in emotional stability and the decision-making processes concerning the expression and suppression of urges. Furthermore, the review highlights the significance of Sattvavajaya Chikitsa (mental discipline therapy) as an essential strategy for effectively managing Dharaniya Vega and achieving comprehensive well-being. By integrating Ayurvedic concepts with modern findings on stress and emotional control, this study offers practical guidance for preventing illness and promoting health through conscious emotional management. The results emphasize that fostering mental balance using Ayurveda-based strategies can improve resilience, cognitive clarity, and long-term physiological wellness. Adopting these principles in everyday life can lead to enhanced well-being, affirming Ayurveda's enduring relevance in contemporary healthcare.